Spatial and temporal patterns of phlebotomine sand flies (Diptera: Psychodidae) in a cutaneous leishmaniasis focus in northern Argentina - Salomón, Oscar Daniel (2004)
Fil: Salomón, Oscar Daniel. ANLIS Dr.C.G.Malbrán. Centro Nacional de Diagnóstico e Investigación en Endemo-Epidemias; Argentina.